Liver abscess caused by Actinomyces odontolyticus: a difficulty diagnostic - case report/ Abcesso hepático causado por Actinomyces odontolyticus: um diagnóstico de dificuldade - relato de caso - Tardin, Rovena Campana (2021)
Actinomyces odontolyticus are slow-growing, facultative anaerobic, gram-positive bacilli and rarely cause liver abscesses. We present a black male, aged 47, with adynamia, jaundice, weight loss, abdominal pain and fever, which started 6 months prior, who was diagnosed with liver abscess and underwent percutaneous drainage, with delayed identification of the pathogen in culture, after three weeks with growth of A. odontolyticus. The literature shows low positivity (10%) in the culture due to its slow growth and technical difficulties; usually positive about two weeks. This is important to alert physicians of the diagnostic possibility and the difficulty of managing it until identification.